Xeroderma Pigmentosum in a Child: An Early Ocular Manifestation (KYAMC Journal, 2024)
A 17 month old boy of first degree consanguineous parents came with the history of poor vision and photophobia. He also had multiple hyper pigmented skin lesions all over the body since 8 months of age. The skin lesions were generalized, hyper pigmented, non-tender, not itchy but photosensitive. Initially the skin lesion was treated by local physicians but when the lesion was spreading, and subsequently when he had developed visual problem, then visited to pediatrician. There was no history of similar type of skin disorder in his family. His developmental millstone was age appropriate. His eyes were sensitive to sunlight and exposure to light causes redness along with poor vision. There was large corneal diameter, conjunctival xerosis, intense photophobia and poor vision in both eyes. Skin survey revealed hyper pigmented macules. Hair and nail apparatus were normal. There was no mucosal or dental involvement, no ulceration or growth elsewhere. Hearing was normal. By a multidisciplinary team this case diagnosed as Xeroderma Pigmentosum clinically. This case managed by proper counselling, advised to protection from sun light and follow up. We like to share our experience of diagnosing and treating this rare case in child with early ocular manifestation.KYAMC Journal Volume: 14, No: 03, October 2023: 175-177.